Pengaruh Pemberian Jus Buah Mengkudu (Morinda citrifolia) dalam Air Minum Terhadap Penampilan Ayam Broiler Jantan - Nurhayati Nurhayati (Jurnal Agripet, 2008)
Effect of noni (Morinda citrifolia) fruit juice in drinking water on male broiler chicken performanceABSTRACT. The present study was conducted to determine the effect of Noni (Morinda citrifolia) fruit juice in drinking water on male broiler chicken performance. The study used 100 male broiler chicken at 3 days of age strain Platinum MB 202 produced by PT. Multi Breeder Adhirama Indonesia (Grup PT Jafpa Comfeed Indonesia) Bandar Lampung. The study was assigned into The Completely Randomized Design with 5 treatments and 4 replications. Chicken were housed in 20 unit colony cages in size 100 x 50 x 50 cm each. The treatments were level of noni fruit juice in drinking water; R0 (control, chicken were not drunk noni fruit juice), R1 (chicken drank water contained 2,5% noni fruit juice), R2 (chicken drank water contained 5% noni fruit juice), R3 (chicken drank water contained 7,5% noni fruit juice) and R4 (chicken drank water contained 10% noni fruit juice). Chicken fed similar ration containing 23.58% crude protein and 3943 kkal/kg gross energy. The selected noni fruit were mature fruit or has color white yellowish. Ration and drinking water were offered ad libitum. During the experiment, chicken were vaccinated only by Vaccine ND on 4 days of age. Chicken were kept for 4 weeks. Parameters measured were feed consumption, drinking water consumption, body weight gain and feed conversion ratio. Collected data were analyzed by analysis of variance and significant effect on the parameters were tested by Duncans Multiple Range Test. Result of this study showed that there was not significant (P0,05) effect noni fruit juice in drinking water on feed consumption, drinking water consumption, body weight gain and feed conversion ratio. It is concluded that noni fruit juice could be mixed into the drinking water of broiler chicken up to 10%.